2020
DOI: 10.1186/s13027-019-0268-z
|View full text |Cite
|
Sign up to set email alerts
|

HPV-related oropharyngeal cancer prevalence in a middle eastern population using E6/E7 PCR

Abstract: Background: Given the paucity of data and widely variable rates that have been reported, the main objective of this study was to examine the prevalence of HPV-positivity in oropharyngeal squamous cell carcinoma (OPSCC) in Middle Eastern patients presenting to one of the region's largest tertiary care centers using polymerase chain reaction (PCR) amplification of the HPV E6/E7 oncogenes, a highly sensitive and specific method of detection. Methods: Medical charts and archived pathological specimens were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…In this regard, it is important to mention that the sample size in our study is similar to that in the previously mentioned evidence. For example, Maroun et al, 2020 used a sample of 34 patients diagnosed with HNSCC to estimate the prevalence of HPV infection in a Lebanese subpopulation, while, Jaber et al, 2019, studied a sample of 45 for the same purpose in Saudi Arabia [23,24]. Accordingly, it is more likely that this variation in the reported HPV prevalence in these studies is attributed to differences in sociocultural behavior, the sensitivity of detection methods, and genetic predisposing factors.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is important to mention that the sample size in our study is similar to that in the previously mentioned evidence. For example, Maroun et al, 2020 used a sample of 34 patients diagnosed with HNSCC to estimate the prevalence of HPV infection in a Lebanese subpopulation, while, Jaber et al, 2019, studied a sample of 45 for the same purpose in Saudi Arabia [23,24]. Accordingly, it is more likely that this variation in the reported HPV prevalence in these studies is attributed to differences in sociocultural behavior, the sensitivity of detection methods, and genetic predisposing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Lawson et al. concluded that a causal role for HPVs in prostate cancer is highly likely which suggests that the HPV vaccine may also be relevant for future prostate cancer research ( 98 ).…”
Section: Hpv Vaccinementioning
confidence: 99%
“…However, recent publications converge in stating that HPV probably has a role in determining SNSCC and implies a better prognosis compared to HPV-negative tumors [ 10 , 11 , 12 ]. In a similar fashion, Epstein–Barr virus (EBV) has been detected in a relevant proportion of SNSCCs [ 13 , 14 ]. However, since a similar proportion of EBV infection was observed in nasal polyps, its role in SNSCC carcinogenesis is questionable [ 14 ].…”
Section: Introduction and Epidemiologymentioning
confidence: 99%
“…In a similar fashion, Epstein–Barr virus (EBV) has been detected in a relevant proportion of SNSCCs [ 13 , 14 ]. However, since a similar proportion of EBV infection was observed in nasal polyps, its role in SNSCC carcinogenesis is questionable [ 14 ].…”
Section: Introduction and Epidemiologymentioning
confidence: 99%